The role of regional anesthesia techniques in the treatment of lumbosacral plexopathy after aorto-femoral bifurcation prosthetics (clinical case) - K. V. Paromov; D. A. Svirskii; L. A. Neledova; M. Yu. Kirov (Вестник анестезиологии и реаниматологии, 2024)
The objective was to demonstrate the effectiveness of regional anesthesia techniques in the treatment of ischemic lumbosacral plexopathy after vascular surgery.Introduction. The frequency of ischemic complications after infrarenal aortic surgery is less than 1%. The persistence and severity of neurological symptoms, as well as the low effectiveness of therapy, can negatively affect the result of surgical intervention.Materials and methods. A 66-year-old patient on the first day after an elective simultaneous aorto-femoral bifurcation prosthetics and cholecystectomy due to an aneurysm of the infrarenal aorta and calculous cholecystitis under inhalation anesthesia had symptoms of left-sided lumbosacral plexopathy, manifesting with left-sided inferior monoplegia, mosaic sensitivity disorders and severe pain syndrome.Results. During routine pain therapy (acetaminophen, nonsteroidal anti-inflammatory drugs, opioids), on the second day after surgery, a transverse abdominis plane block (TAP-block) on the right side and pericapsular nerve group block (PENG-block) on the left side were performed, that led to a rapid regression of acute postoperative pain and restoration of patient mobility. On the 7th, 11th and 16th days after surgery, neurotrophic therapy and comprehensive rehabilitation were supplemented with interventional pain therapy techniques, which provided not only effective pain relief, but also rapid improvement of neurological symptoms. On the 22nd day of postoperative period, the patient was discharged from the hospital with slight motor deficit in the left leg.Conclusions. The case describes complicated course of the postoperative period after aorto-femoral bifurcation prosthetics and cholecystectomy and effectiveness of the interventional therapy for lumbosacral plexopathy of ischemic origin. This strategy led to a rapid regression of neurological deficit in parallel with relief of acute postoperative pain and expansion of rehabilitation opportunities.